Navigating Patriarchy and Piety: A Case Study of Islamic Feminist Discourse and Women's Leadership in Malaysian NGOs - Amina Azhigali; Nina Anis; Rina Farah (Yayasan Adra Karima Hubbi, 2025)
Patriarchal norms continue to shape socio-religious expectations for Muslim women in Southeast Asia, particularly in Malaysia, where debates around gender, authority, and piety intersect within civil society spaces. Islamic feminist discourse has gained increasing visibility in recent years, yet questions remain regarding how women leaders in Muslim-majority contexts negotiate religious legitimacy while challenging gendered power structures. Malaysian non-governmental organizations (NGOs) provide an important arena for examining the everyday strategies through which women navigate patriarchal constraints and articulate faith-based approaches to gender justice. This study aims to investigate how women leaders in Malaysian Islamic-oriented NGOs engage with Islamic feminist discourse to negotiate authority, cultivate legitimacy, and advance transformative social agendas. The research seeks to identify the discursive, religious, and organizational strategies that enable or hinder women’s leadership within patriarchal environments. A qualitative case-study approach was employed, drawing on in-depth interviews with fifteen female NGO leaders, participant observation of organizational activities, and document analysis of mission statements, program materials, and public advocacy texts. Data were analyzed using thematic coding informed by feminist theory, Islamic gender ethics, and discourse analysis. Findings reveal that women leaders strategically mobilize Qur’anic principles, prophetic narratives, and concepts of justice to challenge patriarchal interpretations while maintaining religious credibility. Participants reported using relational leadership styles, community-based legitimacy, and interpretive flexibility to navigate gendered expectations. The study concludes that Islamic feminist discourse serves as both a protective shield and a transformative tool, enabling women to assert leadership within constraints while promoting more inclusive understandings of Islam in civil society.